Kolaborasi Guru dan Orang Tua dalam Penanganan Anak ADHD dengan Speech Delay pada TK Sakinah 1 Cibadak Sukabumi - Agustriani, Asri; Fauziah, Afra Nazwa; Ismayani , Irna; Novianti, Adelia; Fauzia, Isni Sri; Silviawati (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This research examines the collaboration between teachers and parents in handling children with ADHD and speech delay at TK Sakinah 1 Cibadak Sukabumi. Using a qualitative approach with descriptive methods, this study involved classroom teachers, special education teachers, parents, and the school principal as research subjects. Data collection was conducted through participatory observation, in-depth interviews, documentation study, and Focus Group Discussion. The results show that the systematic collaboration pattern implemented, including Individual Learning Programs and consistent handling strategies, has a positive impact on children’s language development, behavioral control, and social interaction. Challenges in program implementation can be overcome through training, written guidelines, and technology utilization. This collaboration model not only improves child development but also enhances teacher competence and parental role in the educational process.